THE PROBLEM OF ASSESSING RESERVES ACCOUNTING ACCORDING TO FSBU 5/2019 "INVENTORIES" - Антышева, Елена; Павлова, Наталья (SWorldJournal, 2021)
The article discusses the legal regulation of accounting transactions for the movement of inventories. In the article was studied the Russian regulations governing the accounting of the movement of stocks. Comparative characteristics between the old and